2008
DOI: 10.1097/hjr.0b013e3283030a97
|View full text |Cite
|
Sign up to set email alerts
|

Effects of drug, biobehavioral and exercise therapies on heart rate variability in coronary artery disease: a systematic review

Abstract: Pharmacologic, biobehavioral and exercise strategies for secondary prevention of CAD significantly increase HRV. This review provides a framework to assist efforts to evaluate the contribution of HRV change to CAD prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
2
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 101 publications
(82 citation statements)
references
References 44 publications
3
74
2
3
Order By: Relevance
“…23 The present trial extends these findings by demonstrating this therapeutic effect in association with reduced ambulatory SBP and PP among subjects with hypertension. This outcome was observed after only an 8-week intervention, which may underestimate a potential benefit of BNT for long-term prognosis.…”
Section: Nolan Et Al Behavioral Neurocardiac Training and Hypertensionsupporting
confidence: 60%
“…23 The present trial extends these findings by demonstrating this therapeutic effect in association with reduced ambulatory SBP and PP among subjects with hypertension. This outcome was observed after only an 8-week intervention, which may underestimate a potential benefit of BNT for long-term prognosis.…”
Section: Nolan Et Al Behavioral Neurocardiac Training and Hypertensionsupporting
confidence: 60%
“…The decrease in HF values and a concomitant change in LF/HF ratio corresponded to a decrease of parasympathetic tone. Both the results of experimental studies in rats and clinical observations in humans and dogs imply that HRV parameters may change during pharmacotherapy of heart failure, irrespective of its etiology (Tacoy et al 2007, Nolan et al 2008, Sal'nikov 2009, Henze et al 2013, Chom-poosan et al 2014, Dias da Silva et al 2015. Consequently, ST-HRV parameters may soon be applied as prognostic and predictive markers in dogs treated due to CMVD.…”
Section: Discussionmentioning
confidence: 99%
“…Prescribed medication included all drugs taken in the previous 14 days that were prescribed by a doctor such as analgesics, antihyperlipidemic agents, antidiabetic agents, psychotropic agents, and antibiotics. We distinguished between beta blockers (British National Formulary codes, chapter 2.4) and other prescribed medications because previous studies have shown the former to have a beneficial effect on HRV levels 36. Other cardiovascular and central nervous system–related medications have been shown to decrease or have no effect on HRV levels 17, 18…”
Section: Methodsmentioning
confidence: 99%